2006
DOI: 10.1177/097325860600100202
|View full text |Cite
|
Sign up to set email alerts
|

Public Relations as a Profession An Analysis of Curricular Content in the United States

Abstract: This study attempts to evaluate the efficacy of undergraduate public relations programmes in the United States. The study surveyed 155 public relations educators and practitioners to determine their impressions on factors such as whether students are being imparted the knowledge and experience to become public relations practitioners, the knowledge and skills respondents thought students ought to possess to become successful professionals, the skills new graduates should possess, and the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
1
0
3
Order By: Relevance
“…In reviewing the literature on the development of public relations as a profession, Sriramesh and Hornaman (2006) concluded that "many authors have advocated the need for specialized training, college education and continuing education as essential to elevate the field to the status of a profession" (p. 157). This conclusion applies to the development of IC as a new profession in the field of communication.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In reviewing the literature on the development of public relations as a profession, Sriramesh and Hornaman (2006) concluded that "many authors have advocated the need for specialized training, college education and continuing education as essential to elevate the field to the status of a profession" (p. 157). This conclusion applies to the development of IC as a new profession in the field of communication.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…PP. en el nivel superior (Matilla, Hernández y Losada, 2010; Observatori de la Càtedra Dircom.Cat, 2010; Xifra, 2007), educación y profesión (Flores, Roca y Tena, 2010;Marques, 2009;Sriramesh y Hornaman, 2006), maestría (Fuentes, 2010) y doctorado (Castillo y Xifra, 2006).…”
Section: Estado De La Cuestiónunclassified
“…• Solo en una universidad española se aborda la multiculturalidad (Sriramesh y Hornaman, 2006) y la comunicación para el desarrollo. En ninguna la migración, los estudios étnicos y feministas (Xifra, 2007) y el community manager.…”
Section: Conclusionesunclassified
See 1 more Smart Citation